Comparison between real‐time tissue elastography and vibration‐controlled transient elastography for the assessment of liver fibrosis and disease progression in patients with primary biliary cholangitis. Issue 12 (7th February 2017) - Koizumi, Yohei; Hirooka, Masashi; Abe, Masanori; Tokumoto, Yoshio; Yoshida, Osamu; Watanabe, Takao; Nakamura, Yoshiko; Imai, Yusuke; Yukimoto, Atsushi; Kumagi, Teru; Takeshita, Eiji; Ikeda, Yoshiou; et al.
Abstract : Aim: Assessing disease progression in patients with primary biliary cholangitis (PBC) is necessary in order to evaluate therapeutic effectiveness. Therefore, the aims of this study were to evaluate both the diagnostic accuracy of both real‐time tissue elastography (RTE) and vibration‐controlled transient elastography (VCTE), and the usefulness of hepatic and splenic elasticity as predictive markers for the progression of symptomatic PBC. Methods: The study participants were 44 patients with PBC. We assessed hepatic and splenic elasticity using RTE and VCTE and measured serum markers related to fibrosis and hepatic and splenic blood flow using Doppler ultrasonography. We then compared RTE and VCTE for diagnostic accuracy. Patients with asymptomatic PBC were followed every 1–3 months. Results: Both RTE and VCTE performed well and had superior diagnostic accuracy compared with biochemical markers. The areas under the receiver operating characteristic curve for RTE and VCTE were 0.92 and 0.92, 0.95 and 0.91, and 0.97 and 0.91 for F ≥ 2, F ≥ 3, and F = 4, respectively. During follow‐up, nine patients (25.0%) developed liver‐related symptoms. Multivariate analysis revealed that splenic elasticity assessed using RTE was a significant independent factor for the development of liver‐related symptoms (odds ratio, 2.19; P = 0.024). Conclusions: Real‐time tissue elastography offered better diagnostic accuracy for severe fibrosis and cholangitis than VCTE. Splenic elasticity determined using RTE is a useful parameter for evaluating liver‐related symptoms and an effective predictive marker of disease progression in patients with asymptomatic PBC.